Decentralized Lending Empirical Analysis of Interest and Liquidation Mechanisms - Schaible, Matthias (Wiesbaden : Springer Fachmedien Wiesbaden : Imprint: Springer Gabler, 2022)
This book deals with the concept of Decentralized Lending on the Blockchain. In order to familiarize with the topic, the basic principles of the underlying technology, such as blockchain, smart contracts or the general architecture of Decentralized Finance, are highlighted. More specific points of Decentralized Lending, such as the principle of supplying and borrowing, lending pools and the underlying logic of overcollateralization will be presented in more detail subsequently. Furthermore, the principle of liquidation is explained, with a focus on the underlying reasons for this. The aim is to provide an overview of how Decentralized Loans work and how the interest rates for them are composed. In addition, the empirical part addresses the question of the extent to which price fluctuations of the deposited collateral have an influence on its liquidation. About the author Matthias Schaible completed an apprenticeship as a banker and studied Real Estate Management at Nürtingen-Geislingen University. He then completed his Master's degree in International Finance at the HWR Berlin and is now working as an investment analyst.
Introduction -- Lending on the Blockchain -- Liquidations -- Conclusion.
Keywords: Financial services industry; Financial Services